IOT Based Garbage Monitoring System - S, Deepa (International Journal of Psychosocial Rehabilitation, 2020)
This undertaking IOT Based Garbage Monitoring System is an extremely brilliant framework which assist with keeping our town and urban areas. We see that in our urban areas open dustbins are over-burden and it make unhygienic conditions for individuals and that spot go away from a terrible stench. Do stay away from every one of these things we are going to execute a task IOT based trash checking System. Thus garbage bins are interacted with Arduino base framework having ultrasonic sensor alongside focal framework demonstrating the Current status of trash in plain view and internet HTML page with Wi-Fi module. Thus expand the cleanness in the nation government began the different venture. This venture was useful for administration task of "SWACHH BHARAT ABHIYAN".